Complementarities between local public and private investment in EU regions - Andrea Brasili; Cristina Brasili; Giorgio Musto; Annamaria Tueske (European Investment Bank (EIB), 2023)
This work investigates the role of local public investment in stimulating private investment and in providing support to growth and development. The analysis is based on a combination of datasets, allowing to build an unbalanced panel for 98 NUTS2 European regions in 13 member states, and for Italy specifically, a balanced panel of 21 regions from 2000 to 2019. The empirical analysis includes both PVARs and local projections as a way to gain robustness in results. The main finding is that locally decided public investment correlates positively with private investment in the same area (with no evidence for reverse causality). The impact of public investment seems to be stronger in downturn phases. GDP growth is more sensitive to public investment in education, training and R&D, in public administration operations and in territorial infrastructures. For Italy, the impact on private investment is particularly strong for public investment in education, training and R&D. This highlights the point, rich of policy implication, that local governments may be more attentive and sensible to the needs of the private sector in terms of skills and labor supply composition and adapt to local specific features.
Keywords: C33; E62; H72; 330; Fiscal multipliers; government investment; regional public investment; private investment